Peran Kebijakan Public Dalam Konservasi Sumber Daya Hutan Di Indonesia - Riski Ardila Sari; Riska Devi; Nurhayati Harahap (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Indonesia's 2020-2024 National Medium Term Development Plan (RPJMN) aims to create a prosperous, just and sustainable Indonesia with a middle to upper income level (middle-income country). In this document there are seven development agendas. The Ministry of Environment and Forestry (KLHK) is directly involved in at least four agendas, namely: Strengthening economic resilience for quality and equitable growth; Regional development to reduce inequality and ensure equal distribution of welfare; Improving the quality and competitiveness of human resources; and Environmental development and increasing resilience to unexpected natural disasters and climate change.